Differentiated learning in inclusive educational activities in junior high school - Anisa Firda Khumaira; Sugeng Bayu Wahyono (Research and Social Study Institute, 2025)
This study aims to analyze teacher and student activities in differentiated learning within inclusive education at SMPN 1 Yogyakarta. The research focuses on: (1) how differentiated learning is facilitated in inclusive education for students with disabilities, and (2) the role of teachers in implementing differentiated learning for students with disabilities. This study employed a qualitative case study approach, collecting data through observation, in-depth interviews, and documentation. Data validity was tested through triangulation of techniques and data sources, while analysis was conducted through reduction, presentation, and conclusion drawing stages. The findings indicate that differentiated learning facilitation has been applied through modifications of curriculum, processes, products/assessments, and learning environments. Teachers adapt materials, apply the pull-out model, implement heterogeneous group learning, and conduct individual assessments based on students' abilities. Teachers' roles in implementing differentiation include upholding ethical principles of equal educational rights, providing developmental opportunities for students with disabilities, fostering empathy among regular students, and enhancing self-confidence in students with disabilities. In conclusion, differentiated learning serves as an effective strategy in inclusive education, although its implementation remains limited to the product aspect and relies heavily on Inclusion Support Teachers.